Organic photochemistry - Thompson, M (1978)
The photochemistry of a number of aromatic systems has been studied; - (i) Irradiation of 1,3, 5-tri-t-butylbenzene in neutral methanol yielded 4-methoxy-2, 4,6-exo -tri-t-butylbicyclo [3.1.0] hex-2-ene, together with a previously unreported compound, tentatively identified as a stereoisomer of 4-methoxy-2,4, 6-exo -tri-t-butylbicyclo [3.1.0] hex-2-ene. (ii) Irradiation of 1,3, 5-tri-t-butylbenzene in acidic methanol yielded 1, 2,4-tri-t-butylbenzene and 1, 2, 5-tri-t-butyl-Dewarbenzene only, as primary and secondary photoproducts respectively. The primary rearrangement process is considered in detail and is shown to be intramolecular by 13C-labelling techniques; a mechanism involving the protonation of a benzvalene is proposed. (iii) The photorearrangement in the gas phase of the six dimethylpyridine isomers has also been investigated. It is shown that the six isomers may be divided into two groups of three, 2, 5-, 2,4- and 3, 5-dimethylpyridine and 2, 6-, 2,3-, and 3,4 dimethylpyridine. Within each group, photolysis of one isomer leads to the formation of the other two isomers as major products. The rearrangement is shown to be intramolecular and a mechanism is proposed in which the nitrogen atom effectively inserts itself between any two carbon atoms in the aromatic nucleus. (iv) The photochemistry of the six N-methyl-dimethylpyridinium chlorides is also considered. Preliminary data suggests that photorearrangement of these compounds may occur by a mechanism analogous to that for the dimethylpyridines.